Ultrasound guidance for central venous catheter placement in Australasian emergency departments: Potential barriers to more widespread use - Matera, J.; Egerton-Warburton, Diana; Meek, R. (2010)
Objectives: To survey Fellows of the Australasian College for Emergency Medicine (FACEMs) in order to describe current ultrasound (US) usage during central venous catheter (CVC) placement and to compare practice and opinions between FACEMs routinely using US and those not.Methods: Descriptive and analytical cross-sectional electronic survey of all FACEMs. Baseline variables including hospital type, US availability, frequency of CVC insertion, US usage and technique are presented descriptively. US practice and opinions on usage are compared between routine and non-routine users.Results: Responses were obtained from 486 (42.4%) of 1146 FACEMs emailed. Whereas 88.5% of respondents had US available and 70% had done an US course, only 37% routinely used US for CVC placement. Completion of an US course and performance of >11 CVC per year were strongly associated with routine US use (odds ratio 10.0 [5.5-18.4] and 2.6 [1.7-3.9], respectively). Common barriers to more frequent US use were not having completed an US course (20%) and US-guided CVC placement taking too long (18%). Eighty-five per cent of FACEMs agreed that there should be ED access to US and US training but only 34% thought its use should be mandatory.Conclusions: We found that only 37% of FACEM respondents routinely used US to guide placement of CVCs and a number of barriers to more frequent use are identified. Practices and opinions regarding US use differed significantly between routine and non-routine users. © 2010 The Authors. EMA © 2010 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine.